Using website creation as a hub, promoted collaborative learning in teacher education - Järnerot, Anna; Lund, Anne Bonnevie (Frontiers in Education, 2025)
IntroductionThe article presents a teaching design used in the first year of a teacher education in Norway. The teacher educators designed, taught and researched the project, evaluating it in collaboration with students. This is in line with a practitioner/action research approach and formative dialogue research. The teaching design was centered around the making of websites as a form of wiki learning. 143 students participated in the project. This article focuses on the student perspective and the data material was gathered through a survey and reflection papers.ResultsThe students pointed out the collaboration as the most important learning and how that prepared them for the future teacher profession. The student statements were classified into three categories of professional growth and discussed using the theory of professional capital. Using the students’ comments and the teacher educators’ experience, the teaching design is discussed up against earlier designs of wiki learning. The discussion elaborates on 6 possible success factors.